ASSESSING THE DETERMINANTS OF INTERNAL AUDIT EFFICIENCY IN THE NIGERIAN PUBLIC SECTOR - TAIWO, Isaac Babatope (IJRDO - Journal of Business Management, 2019)
The study assessed the internal audit efficiency of the public sector in Nigeria with a view of its major determinants. The data used were collected from primary sources of which two ministries were selected using a purposive sampling technique because they had almost the same structural and operational characteristics in their internal audit structures. Data gathered were proportionately stratified through random sampling technique, descriptive statistic and Z-test was used for data analysis. The results of the analysis shown that (Z-test is greater than the critical value, Compute value > critical value i.e. 13.546 >1.98) internal audit efficiency has a significant effect on the performance of the Nigerian public sector. The results from the respondents to the determinants in the area of the incidence of irregularities by the appropriate authorities, flaw of audit model and accounting system, inadequacy of the internal control system and known- implementations of routine audit report has contributed to the challenges of internal audit efficiency Based on the findings on these determinants, internal audit in Nigerian has contributed to the challenges of inefficiency of the internal audit performance in the public sector and the internal audit functions are conducted in conformance with the International Standards for the Professional Practices in Auditing.